Brown Trout Removal Effects on Short‐Term Survival and Movement of Myxobolus cerebralis‐Resistant Rainbow Trout. Issue 3 (28th April 2015) - Fetherman, Eric R.; Winkelman, Dana L.; Bailey, Larissa L.; Schisler, George J.; Davies, K.
Abstract: Following establishment of Myxobolus cerebralis (the parasite responsible for salmonid whirling disease) in Colorado, populations of Rainbow Trout Oncorhynchus mykiss experienced significant declines, whereas Brown Trout Salmo trutta densities increased in many locations across the state, potentially influencing the success of M. cerebralis ‐resistant Rainbow Trout reintroductions. We examined the effects of Brown Trout removal on the short‐term (3‐month) survival and movement of two crosses of reintroduced, M. cerebralis ‐resistant Rainbow Trout in the Cache la Poudre River, Colorado. Radio frequency identification passive integrated transponder tags and antennas were used to track movements of wild Brown Trout and stocked Rainbow Trout in reaches where Brown Trout had or had not been removed. Multistate mark–recapture models were used to estimate tagged fish apparent survival and movement in these sections 3 months following Brown Trout removal. A cross between the German Rainbow Trout and Colorado River Rainbow Trout strains exhibited similar survival and movement probabilities in the reaches, suggesting that the presence of Brown Trout did not affect its survival or movement. However, a cross between the German Rainbow Trout and Harrison Lake Rainbow Trout exhibited less movement from the reach in which Brown Trout had been removed. Despite this, the overall short‐term benefits of the removal were equivocal, suggesting that Brown Trout removal may not be beneficial for the reintroduction of Rainbow Trout. Additionally, the logistical constraints of conducting removals in large river systems are substantial and may not be a viable management option in many rivers.